Moisture and water storage in the soil of four types of vegetation cover - Yaguache Ordóñez, Luis Alfredo (2022)
The objective of this study was to evaluate soil moisture in four environments: native forest (Cerrado native de Mata Atlântica), pasture, pine plantation and cultivated soil. For analysis of humidity and water content in the soil, it was necessary to collect 20 undeformed samples monthly for each type of cover, in five depth bands 0-5 cm, 5-30 cm, 30-50 cm, 50-80 cm and 80-100 cm. The study revealed that the superficial strip has the lowest moisture percentage of the entire soil profile, while the deepest stratum 80 to 100 cm presented the highest moisture values. On the other hand, the soil covered by the native Cerrado of Mata Atlântica presented the highest percentage of moisture and the highest content of water stored in the soil; therefore, it is concluded that the surface strip is the one that presents the greatest variability in soil moisture because it is located in the evaporable zone or with the greatest exposure to solar radiation; consequently, as the depth increases, the greater the storage of water in the soil; On the other hand, the coverage analogous to a primary forest presents the highest percentage of humidity and water storage in the soil.